Gender Empowerment Indicators: Better Management Of Resources To Optimize Results (Economic and Bussiness Faculty, Dr Soetomo University, 2017)
Abstract.As a cultural anthropologist I strongly believe in the value of applied anthropology especially when it comes to international cooperation and development. Thanks to a methodology principally based on participant observation I found that anthropologists benefit from a deep understanding of the social dynamics within a group. In this working paper I discuss my work for AIDA, a Spanish NGO, in Dhaka. Several years ago, I was called to collaborate with this organization in order to set ‘gender empowerment indicators’ for their projects. The activities, approved and financed by AIDA, were implemented by Tarango, a local NGO. The main goal of AIDA was to improve the conditions of women in specific urban and rural areas of Bangladesh. Women are seen by the international community as one of the major driving forces in the development of a country. Gender equality and the empowerment of women have been defined by The Millennium Development Goals Report as ‘preconditions for overcoming poverty, hunger and disease’ (UN 2010, p.4).What I have found extremely interesting while working at Tarango was the strict relationship between economic and gender empowerment, social capital and creativity. I found that being aware of the positive externalities of this relationship can lead to a more efficiently organized production, economic independence and most importantly a stronger sense of identity.